Game-based learning intervention: the effect of baamboozle on science learning interest in primary education - Safrizal; Reva Selpia; Kavita Arafah; Jamiu Temitope Sulaimon (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This study aims to analyze the effectiveness of the educational game Baamboozle as a gamification intervention in enhancing learning interest in Science and Social Studies (IPAS) among fifth-grade primary school students. This research is motivated by the existing challenge of low student interest and engagement in IPAS, often exacerbated by the dominance of conventional teaching methods, which fail to counter student apathy and concentration decline, particularly during post-recess sessions.The methodology adopted was quantitative, quasi-experimental, with a nonequivalent control group posttest-only design, and a total sample of 45 students from the accessible population.Data was collected via a 20-item Likert scale questionnaire (Cronbach’s alpha = 0,956). The results demonstrate that the experimental group achieved a higher mean score (M = 75.82) than the control group (M = 57.27).The t-test yielded t(43) = 0,000, p < .001, confirming a significant difference in learning interest. The effect size was calculated as Cohen’s d = 5.14, indicating a large effect. This suggests that Baamboozle serves as an interactive, collaborative tool that supports student engagement, aligning with constructivism and the ARCS motivation model. This research contributes to educational science by providing empirical data regarding the use of accessible digital gamification to foster learning interest in primary education.